One-step direct synthesis of layered double hydroxide single-layer nanosheets1. Issue 21 (7th June 2015) - Yu, Jingfang; Martin, Benjamin R.; Clearfield, Abraham; Luo, Zhiping; Sun, Luyi
<x xml:space="preserve">Abstract</x> Colloidal layered double hydroxide (LDH) single-layer nanosheets were directly synthesized via a one-step process, instead of the conventional exfoliation approach.